Regulation barriers for the insertion of renewable energies in small-scale distributed generation systems, Nicaragua case of study (Nexo Revista Científica, 2021)
In this article, different barriers that are presented as a challenge to improve for the insertion of Renewable Energies (RE) in small-scale distributed generation systems were detected and analyzed using the grounded theory and the computer tool Atlas ti 7. It was found that the regulatory framework should be improved to make private investment in Renewable Energies (RE) in distributed generation systems attractive and it was possible to identify different types of barriers to the use of renewable energies in the electrical networks of power distribution companies based on to the Nicaraguan case study.